Communication as lifeline communication strategies in the withdrawal from suicidal ideation - Botor, Jephan Borja 1991-
"Despite the increasing trend of suicide rates in the Philippines, suicide is till underreported and misclassified because of the stigma attached to it. With communication considered as vital in most, if not all, aspects of individual's life, it could also be important in helping Filipino teenagers contemplating suicide. Thus, this study aims to explain the interplay of intrapersonal and interpersonal strategies in every stage of withdrawal from suicidal ideation. Through textual analysis, focus and key informant interviews, we found out that there are three phases in withdrawal from suicidal ideation which we derived from the Cognitive Dissonance Theory, namely: 1) Psychological discomfort; 2) Addition of consonant belief and reduction of dissonant beliefs; and 3) Change of dissonant beliefs. Interpersonal communication helped in delaying suicide in the first phase of withdrawal from suicidal ideation through messages, verbal and non-verbal, that contradicted the negative thoughts that occur in the teenager's intrapersonal communication. Because of the contradiction, the suicidal teenager experienced psychological discomfort in the initial phase. People onvolved and the messages in interpersonal communication affect the process more than the medium does. The message had to be something that implicitly disturbed the conscience of the teenager, while the people involved had to be the loved and respected figures in the lives of the teenagers. On the other hand, intrapersonal communication functioned to let the suicidal teenager release, process and analyze thoughts. The most commonly used medium was rumination. Other methods were journal and diary-keeping, blogging, praying and painting. After the first phase of withdrawal wherein intrapersonal communication works with interpersonal communication, the rest of the phases are left for though-processing and decision-changing through intrapersonal communication. After all the three phases, the teenager either withdrew from suicidal ideation by completely abandoning suicidal thought, or just delayed suicide for some time. In the latter case, the teenager had to go over the three phases again, but each time, with increased capability to adapt to invalidate negative thoughts and to further delay suicide, which will aid him or her to completely withdraw from suicidal ideation later on."